THE EFFECT OF TIKTOK APPLICATION ON STUDENTS’ VOCABULARY MASTERY - Novita Utamy , Ega; Haryanto, Endang; Riswanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Vocabulary mastery is a fundamental component in learning English as a foreign language, as it supports students’ abilities in listening, speaking, reading, and writing. However, many junior high school students experience difficulties in acquiring sufficient vocabulary due to monotonous teaching methods and limited exposure to engaging learning media. Therefore, this study aims to investigate the effect of using the TikTok application on students’ vocabulary mastery. This research employed a quantitative approach using a quasi-experimental design with a pre-test and post-test. The population of this study consisted of eighth-grade students of SMPN 5 Bengkulu City in the academic year 2024/2025, with class VIII G comprising 33 students selected as the experimental group through purposive sampling. The treatment was conducted by integrating TikTok videos containing English vocabulary materials into the teaching and learning process over six sessions. The data were collected using vocabulary tests and analyzed using statistical analysis. The results showed a significant improvement in students’ vocabulary mastery after being taught using the TikTok application. The findings indicate that TikTok is an effective and engaging digital learning medium that can enhance students’ vocabulary acquisition and learning motivation. Therefore, it is recommended that English teachers integrate social media platforms such as TikTok into vocabulary instruction to create more interactive and meaningful learning experiences.